2022
DOI: 10.1021/acsami.2c11339
|View full text |Cite
|
Sign up to set email alerts
|

Solid Electrolyte–Cathode Interface Dictates Reaction Heterogeneity and Anode Stability

Abstract: Solid-state batteries (SSBs) employing a lithium metal anode are a promising candidate for next-generation energy storage systems, delivering higher power and energy densities. Interfacial instabilities due to non-uniform electrodeposition at the anode−solid electrolyte (SE) interface pose major constraints on the safety and endurance of SSBs. In this regard, non-uniform kinetic interactions at the anode−SE interface which are derived from cathode microstructural heterogeneity can have significant impact on an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…This implies that the synergistic effect from our composite separator and CNT host anode would be a potential solution for utilizing Li metal as an anode. One of the previous studies revealed that the microstructural heterogeneity of the cathode, which is induced by the compositional ratio and particle sizes of the active material, has a significant effect on spatially uneven current and Li + transport during charging/discharging . Therefore, it is anticipated that further Li + flux delocalization could be obtained when the cathode design is configured along with our proposed separator/anode pair.…”
Section: Resultsmentioning
confidence: 97%
“…This implies that the synergistic effect from our composite separator and CNT host anode would be a potential solution for utilizing Li metal as an anode. One of the previous studies revealed that the microstructural heterogeneity of the cathode, which is induced by the compositional ratio and particle sizes of the active material, has a significant effect on spatially uneven current and Li + transport during charging/discharging . Therefore, it is anticipated that further Li + flux delocalization could be obtained when the cathode design is configured along with our proposed separator/anode pair.…”
Section: Resultsmentioning
confidence: 97%
“…As confirmed in the low‐stack‐pressure experiment, the relatively high uniformity of the pore size can lead to a homogeneous cathode reaction within the electrode, and it may have helped to maintain a uniform ionic transport pathway at the CA|CA interface during long‐term cycling. In addition, because the non‐uniformity of the reaction in the cathode can lead to reaction heterogeneity at the anode/SE interface according to a recent report, [ 63 ] the larger anode/SE interfacial resistance of the bare NCM may be the result of cross‐talk caused by the reaction heterogeneity at the cathode side.…”
Section: Resultsmentioning
confidence: 99%
“…The role of electric energy storage technologies, i.e., batteries, is ever-increasing. Recently, the concept of the solid-state battery (SSB) has been attracting strong interest as it has the potential to further advance lithium-ion battery technology. The ultimate target for the anode material is lithium metal due to its low redox potential of E H = −3.04 V and high theoretical capacity of q th = 3861 mAh/g. , The successful implementation of the reversible lithium metal anode concept, however, is hampered especially by morphological instabilities at the metal anode interface and dendrite formation due to inhomogeneous metal dissolution and deposition. This places high demands on potential solid electrolyte (SE) separator materials. These demands include, e.g., ensuring homogeneous current flow, compensating for volume changes at the interface, and providing high mechanical resistance to dendrite growth.…”
Section: Introductionmentioning
confidence: 99%